Introduction to hospitality management - Walker, John R (Pearson Prentice Hall, 2015)
"Tomorrow's managers are off to a strong start with this fully updated and streamlined edition. Each chapter includes an increased emphasis on globalization and environmental responsibility and a new chapter on Events Marketing appears in Part V. The practicality of previous editions continues with mini-case studies, contributions from industry experts, profiles of corporations, profiles of hospitality professionals and a new student DVD-ROM packed with resources to support readers' coursework and their careers. It covers tourism, lodging, restaurants, managed services, beverages, conventions and meeting, and leisure/recreation; in addition to examining gaming entertainment, marketing and human resources, and leadership and management. For individuals interested in a hospitality industry career.--Publisher's description.